Giant congenital melanocytic nevus of the back: a case report (Universa Medicina, 2024)
BackgroundGiant congenital melanocytic nevus (GCMN) is a rare disease with an extremely low incidence, that is present from or develops at birth and typically affects the dermis but may also affect other skin layers. Its incidence is estimated at